Sistem Pendukung Keputusan Pemberian Insentif Berdasarkan Penilaian Kinerja Aparat Desa Menggunakan Metode Multi Attribute Utility Theory - Bahrin Dahlan; Betrisandi (Universitas Negeri Gorontalo, 2022)
The purpose of This research is to generate incentives based on performance assessment, which creates a good and transparent village government. Therefore, the awarding of incentives is based on performance appraisal, in such assessment is required decision support System (SPK) that can take into account all criteria to help facilitate the decision making process. By Implementing the method multy Attribute Utility Theory (MAUT) with the criteria that have been applied to theoffice of Puncak Jaya village namely Performance Assessment, attendance, discipline, responsibility on the service. The resulting system is the calculation value ofincentives for incentive based on the performance assessment of the village apparatus with the method of multy Attribute Utility Theory (death). Based on research the decision support system that has been made can help decision makers in determining the incentive grant of village apparatus. This is evidenced by the test result done by the Black Box method and The testing base Path that generates the value V (G) = CC, where V (G) = 4 and CC = 4, so it is obtained that the logic ofa flowchart calculation of the normalization and Perankingan are correct and based on Black Box testing which includes the test input process and output with reference to the draft software has been fulfilled with the results according to the design.